Sovereign Borrowing by Developing Countries : What Determines Market Access? - Gelos, R. (IMF Working Papers; Working Paper ;, 2004)
What determines the ability of governments from developing countries to access international credit markets? We examine this question using detailed data on sovereign bond issuances and public syndicated bank loans since 1982. We find that traditional measures of a country's links with the rest of the world (such as trade openness) and traditional liquidity and macroeconomic indicators do not help much in explaining market access. However, a country's vulnerability to shocks and the perceived quality of its policies and institutions appear to be important determinants of its government's ability to tap the markets. We are unable to detect strong punishment of defaulting countries by credit markets.